ASSESSMENT AND DEVELOPMENT OF MOTIVATIONAL MECHANISMS FOR ATTRACTING AND RETAINING HUMAN RESOURCES IN ENTERPRISES UNDER WARTIME AND POST-WAR CONDITIONS - Bryukhovetskaya, Nataliya; Iievlev, Viktor (SWorld-Ger Conference proceedings, 2025)
This paper examines employee motivation and stimulation as measures implemented to attract and retain personnel at enterprises operating under human resource shortages caused by the military actions in Ukraine. This context necessitates the development of